Strategi Pemasaran Produk Pada BPRS Insan Cita Parung Dengan Pendekatan Analisis SWOT Dan AHP - aldi fathurrahman; Nurlis Azhar (Indonesian Journal of Economics Application (IJEA), 2019)
This study analyzes the marketing strategy of financial product in BPRS Insan Cita in Parung Bogor. The expected result of the research is to determine the alternative marketing strategies and priority marketing strategies using SWOT and AHP analysis. Both analyzes are used to identify the strengths, weaknesses, opportunities and threats of the company, determine the company's strategy based on external and internal factors of the company and get the priority strategy. The results showed that the goal of the product marketing strategy was to increase customers with the right alternative strategy namely to improve marketing and socialization of BPRS Insan Cita products, improve product innovation, improve quality and service quality and strategies to expand market share.